Erratum: Hubungan Asupan Energi, Zat Gizi Makro dan Mikro terhadap Kebugaran Atlet Dyva Taekwondo Centre Cibinong - Mury Kuswari; Fitri Handayani; Nazhif Gifari; Rachmanida Nuzrina (JUARA : Jurnal Olahraga, 2020)
Correction to: JUARA: Jurnal Olahraga This corrects the article DOI: https://doi.org/10.33222/juara.v5i1.572 This article was originally published using English metadata in the article title and this is our fault. but now the article metadata has been changed in Indonesian and appears correctly in the current article.